Kalanchoe ×forbesiae (Crassulaceae subfam. Kalanchooideae) derived from K. lubangensis × K. sexangularis: towards improved horticultural material - Smith, Gideon F.; Hankey, Andrew (Phytotaxa, 2021)
Efforts to broaden and improve the genetic stock from which horticultural material of Kalanchoe (Crassulaceae subfam. Kalanchooideae) is made available globally are on-going. Apart from making small, light-weight, highly floriferous material—both single- and double-flowered—available to the in- and outdoor plant trades, work is also underway to select Kalanchoe material that can be sold as long-lasting cut flowers. Material derived from K. lubangensis × K. sexangularis, here described as K. ×forbesiae, shows promise as a source of cut flowers.